Porous coordination network crystal for guest molecule analysis, and method for determining molecular structure

By using a coordinated formation of three-branched ligands and connecting molecules with transition metals in the polymetal composite crystal, the free rotation of the 3-pyridine group is inhibited and weak coordination bonds are introduced, which solves the problems of medium molecular analysis and structural fluctuations, and a high-precision and stable analysis platform is achieved.

JP2025069197AInactive Publication Date: 2025-04-30INSTITUTE OF SCIENCE TOKYO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025006237
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-30
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult for the prior art to effectively analyze medium molecules (500-3000 molecular weight) as guest molecules, and structural fluctuations are difficult to suppress during the analysis process, affecting the analysis accuracy.

Method used

Using a polymetal composite crystal with a three-dimensional network structure, the coordinated formation of the three-branched ligand and the connecting molecules with the transition metal is inhibited, and the free rotation of the 3-pyridine group is introduced into the crystal through weak coordination bonds to reduce structural fluctuations.

Benefits of technology

A large pore-size polymetal composite crystal is realized, providing a high-precision platform for medium molecular analysis, while at the same time, the stability and accuracy of the analysis are improved by suppressing structural fluctuations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069197000001_ABST
    Figure 2025069197000001_ABST
Patent Text Reader

Abstract

To provide a porous coordination network crystal for guest molecule analysis having a large pore size and capable of suppressing structural fluctuation, a method for preparing a sample for crystal structure analysis, and a method for determining the molecular structure.SOLUTION: In the porous coordination network crystal for guest molecule analysis, pores including guest molecules are formed, and a three-dimensional network structure is constituted by tridentate ligands 2 and connector molecules 4 coordinated to a transition metal 3. The tridentate ligands 2 are of a three-branched structure represented by the general formula (I), in which nitrogen atoms of 3-pyridyl groups function as ligating atoms. (In the formula, W represents an aromatic group which may comprise heteroatoms.)SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous network complex crystal for guest molecule analysis, and further to a method for preparing a sample for crystal structure analysis and a method for determining a molecular structure, utilizing the porous network complex crystal. [Background technology]

[0002] Porous coordination networks (PCNs) consisting of metal ions and organic ligands have infinite structures that can maintain their structure even after the solvent is removed, and technologies that utilize these pores have been proposed. For example, PCNs that undergo reversible structural changes in response to the adsorption and desorption of guests in the pores (Non-Patent Document 1), PCNs that combine 2,4,6-tris(4-pyridyl)triazine ligands with ZnBr2 (Non-Patent Documents 2, 3), and tripyridylhexaazaphenalenate (K + TPHAP - A PCN combining the ligand 2,4,6-tris(3-pyridyl)hexaazaphenalenate with ZnI2 has been reported (Non-Patent Document 4). The present inventors have also recently reported a synthesis example of a PCN using the ligand 2,4,6-tris(3-pyridyl)hexaazaphenalenate with cobalt(II) chloride and terephthalic acid (Non-Patent Document 5). [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] Sujit K. Ghosh et al., Angew. Chem., 2013, 125, 1032 [Non-Patent Document 2] Masaki Kawano et al., Angew. Chem. Int. Ed. 2008, 47, 1269 -1271 [Non-Patent Document 3] Makoto Fujita et al. NATURE CHEMISTRY, VOL 3, 2011 [Non-Patent Document 4] Masaki Kawano, et al. CrystEngComm., 2014, 16, 6335 [Non-Patent Document 5] Masanori Kono et al., "Synthesis of network complexes by controlling the substituents of multipoint interacting ligands," Proceedings of the Annual Meeting of the Crystallographic Society of Japan, November 2018, PB-I-04. Summary of the Invention [Problem to be solved by the invention]

[0004] PCN has a very large surface area compared to zeolite and activated carbon, and isostructures can be generated by customizing the structure, so it is attracting attention in the fields of catalyst support, adsorption, and separation and purification. In addition, if PCN crystals that can be used to analyze guest molecules can be provided, especially if PCN crystals that can analyze medium molecules (molecules with molecular weights of about 500 to 3000), which have been considered difficult to analyze until now, it is expected that drug development will be dramatically accelerated. However, in order to incorporate medium molecules as guest molecules, it is necessary to increase the pore size. In addition, it is desirable to suppress the structural fluctuation of PCN crystals in order to improve the accuracy of analysis.

[0005] Although the above describes the case where a medium-sized molecule is used as the guest molecule, the same problem can arise regardless of the molecular weight.

[0006] The present invention has been made in view of the above background, and has as its first object to provide a porous network complex crystal for guest molecule analysis that has a large pore size and is capable of suppressing structural fluctuation, a method for preparing a sample for crystal structure analysis, and a method for determining a molecular structure. The second object is to provide a porous network complex crystal that can be used for purposes other than analysis. [Means for solving the problem]

[0007] As a result of extensive investigations, the present inventors have found that the problems of the present invention can be solved in the following aspect, and have thus completed the present invention. [1]: A porous network complex crystal for guest molecule analysis, It has a three-dimensional network structure and has pores that contain guest molecules. the three-dimensional network structure is formed by coordinating a tridentate ligand and a connector molecule to a transition metal; The tridentate ligand is a compound having a three-branched structure represented by the following general formula (I) in which the nitrogen atoms of the 3-pyridinyl group each function as a ligand (wherein W is an aromatic group which may contain a heteroatom): [ka] the connector molecule is a bidentate ligand, and the angle between each ligand of the bidentate ligand and the center of gravity of the connector molecule is 70 to 180°; A porous network complex crystal for analyzing guest molecules in which the free rotation of the 3-pyridinyl group axis is restricted. [2]: The porous network complex crystal for guest molecule analysis described in [1], wherein a solvent molecule is further coordinated to the transition metal, and the coordinate bond between the transition metal and the solvent molecule is weaker than the coordinate bonds between the transition metal and the tridentate ligand and between the transition metal and the connector molecule. [3]: The porous network complex crystal for guest molecule analysis according to [1] or [2], wherein the transition metal is a divalent metal. [4]: The porous network complex crystal for guest molecule analysis described in any one of [1] to [3], wherein the pores include honeycomb-shaped pores and pores smaller in size than the honeycomb-shaped pores that connect the honeycomb-shaped pores to each other. [5]: The porous network complex crystal for analyzing guest molecules according to any one of [1] to [4], wherein the tridentate ligand is represented by general formula (II): [ka] In the formula (II), X is selected from the group consisting of the compounds represented by the formula (III) and the compounds represented by the formula (IV), and Y 1 ~Y 3are each independently selected from a single bond, a carbon-carbon double bond, and a carbon-carbon triple bond directly connecting X to the 3-pyridinyl group. [ka] However, Z in the general formula (III) 1 ~Z 6 are each independently CH or N. [ka] [6]: The porous network complex crystal for guest molecule analysis according to any one of [1] to [5], wherein the guest molecule has a molecular weight of 500 to 3,000. [7]: Prepare a sample by dissolving the target compound in a solvent. The sample is Dispersing the porous network complex crystal for guest molecule analysis according to any one of [1] to [6]; A method for preparing a sample for crystal structure analysis, comprising incorporating the compound to be analyzed into the pores of the porous network complex crystal. [8]: A method for determining the molecular structure of a compound to be analyzed, comprising performing crystal structure analysis using a sample for crystal structure analysis obtained by the method for preparing a sample for crystal structure analysis described in [7]. Effect of the Invention

[0008] The present invention has the excellent effect of providing a porous network complex crystal for guest molecule analysis which has a large pore size and is capable of suppressing structural fluctuation, a method for preparing a sample for crystal structure analysis, and a method for determining a molecular structure. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1A is a schematic diagram of a conventional tridentate ligand, and FIG. 1B is a schematic diagram of a tridentate ligand according to the present embodiment. [Diagram 2] FIG. 2 is a schematic structural diagram showing an example of a structural unit of the PCN crystal of the present embodiment. [Diagram 3]FIG. 2 is a schematic structural diagram showing an example of a PCN crystal according to the present embodiment. [Figure 4] FIG. 2 is a schematic diagram for explaining an example of the stereochemical configuration of nitrogen of a 3-pyridinyl group of a tridentate ligand in a PCN according to this embodiment. [Diagram 5] FIG. 2 is a schematic structural diagram showing an example of a bonding state between a transition metal of a PCN and an interlayer connector according to the present embodiment. [Figure 6] (a) Powder X-ray profile of the PCN crystal according to Example 1. (b) Powder X-ray profile after grinding the PCN crystal according to Example 1 in a mortar. (c) X-ray profile of the PCN crystal according to Example 1 obtained by simulation. [Figure 7] 1 is a micrograph of a PCN crystal according to Example 1. [Figure 8] 1 is a structural diagram of the PCN crystal according to Example 1, as viewed from the c-axis direction, determined by X-ray structural analysis. [Figure 9] Structural diagram of the PCN crystal from Figure 8, with the tridentate ligand hidden, viewed from the c-axis direction, determined by X-ray structure analysis. [Figure 10] FIG. 2 is a structural diagram of the PCN crystal of Example 1, determined by X-ray structural analysis with the tridentate ligand hidden and viewed from the b-axis direction. [Figure 11] FIG. 2 is a partially enlarged view of the structure determined by X-ray structural analysis in which part of the DMF in the PCN crystal of Example 1 is replaced with water molecules. [Figure 12] FIG. 2 shows a DTG-DTA profile of the PCN crystal according to Example 1. [Figure 13] FIG. 4 is a structural diagram of a guest molecule (anthracene) trapped in the pores of the PCN crystal in Example 2, determined by X-ray structural analysis. [Figure 14] Absorption spectra over time after adding PCN crystals to a DMF solution of iodine. [Figure 15] This figure shows the change in absorbance over time when a PCN crystal incorporating iodine as a guest was irradiated with UV light. [Figure 16] FIG. 1 is a structural diagram obtained by X-ray structural analysis of a guest molecule (triphenylene) trapped in the pores of the PCN crystal in Example 4. [Figure 17] FIG. 1 is a structural diagram obtained by X-ray structural analysis of a guest molecule (safflower pigment carthamin) trapped in the pores of the PCN crystal of Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] An example of an embodiment to which the present invention is applied will be described below. Note that other embodiments are also included in the scope of the present invention as long as they are consistent with the gist of the present invention. Also, the size and ratio of each part in the following figures are for the convenience of explanation and are not limited to these.

[0011] The porous network complex (hereinafter referred to as PCN) crystal for guest molecule analysis according to this embodiment has a three-dimensional network structure. This three-dimensional network structure is formed by coordinating a tridentate ligand and a connector molecule to a transition metal. In addition, the PCN crystal has pores that encapsulate guest molecules.

[0012] The tridentate ligand is a compound having a three-branched structure represented by the following general formula (I), in which the nitrogen atoms of the 3-pyridinyl group each function as a ligand. [ka] However, W in the formula (1) is an aromatic group which may contain a heteroatom. The nitrogen atoms of the 3-pyridinyl group of the tridentate ligand are each coordinated to a transition metal, and the free rotation of the axis of the 3-pyridinyl group is restricted by this coordination.

[0013] The connector molecule is a bidentate ligand, and the angle between the center of gravity of the connector molecule and each ligand of the bidentate ligand is 70 to 180°. The center of gravity here refers to the center of mass of the connector molecule.

[0014] The tridentate ligand used in the PCN disclosed in the above-mentioned Non-Patent Documents 2 and 3 is 2,5,8-tri(4'-pyridyl)-1,3,4,6,7,9-hexaazaphenalene (4-TPHAP -), which is a compound with a three-branched structure having three 4-pyridinyl groups. The axis of this 4-pyridinyl group rotates freely as shown in Figure 1(a), and as shown in the figure, it has excellent symmetry. Even in PCN, where the nitrogen of this 4-pyridinyl group is coordinated with a transition metal, the free rotation of the axis of the 4-pyridinyl group itself is not hindered.

[0015] In contrast, the tridentate ligand of the PCN crystal used in this embodiment is a compound with a three-branched structure having three 3-pyridinyl groups as ligands, as shown in general formula (I). As shown in FIG. 1(b), this tridentate ligand increases the degree of freedom of the topological structure due to the free rotation of the axis of the 3-pyridinyl group. In other words, by using a tridentate ligand with a three-branched structure having a 3-pyridinyl group, a structure with reduced symmetry can be obtained.

[0016] In addition, in the PCN crystal used in this embodiment, the free rotation of the axis of the pyridinyl group is inhibited by the bond between the nitrogen of the 3-pyridinyl group and the transition metal. By suppressing the free rotation of the 3-pyridinyl group, it is possible to reduce the dynamic motion more than when a tridentate ligand having a three-branched structure with a 4-pyridinyl group is used. As a result, it is expected that the analytical accuracy of the guest molecule will be improved, and that it will be possible to analyze guest molecules that have been difficult to analyze so far. In addition, by using a PCN crystal having a tridentate ligand having a three-branched structure with a 3-pyridinyl group, the opening diameter of the pores can be widened.

[0017] The pores of the three-dimensional network are regularly formed by combining a plurality of tridentate ligands and connector molecules with transition metals via coordinate bonds. The shape of the pores can vary depending on the raw material molecules used. A preferred example is an embodiment including a honeycomb-shaped hole and a hole smaller in size than the honeycomb-shaped hole that connects the honeycomb-shaped holes to each other. The size of the opening diameter of the pores can be easily adjusted depending on the type of tridentate ligand, connector molecule, and transition metal.

[0018] The tridentate ligand is a compound that satisfies the above formula (I) and has three nitrogen atoms of 3-pyridinyl groups as ligands, and is not limited as long as it can form a PCN crystal together with a connector molecule and a transition metal, but it is preferable to use a tridentate ligand that is substantially planar in shape to form a two-dimensional network. In addition, it is preferable that the tridentate ligand is a triangular shape with the 3-pyridinyl group of the tridentate ligand as the vertex. W in formula (1) is preferably a delocalized aromatic plane capable of π-π interaction. The tridentate ligand may be used alone or in combination of two or more types.

[0019] A suitable example of the tridentate ligand is a compound represented by the general formula (II). [ka] In the formula (II), X is selected from the group consisting of the compounds represented by the formula (III) and the compounds represented by the formula (IV), and Y 1 ~Y 3 are each independently selected from a single bond, a carbon-carbon double bond, and a carbon-carbon triple bond directly connecting X to the 3-pyridinyl group. [ka] However, Z in the general formula (III) 1 ~Z 6 are each independently CH or N. [ka]

[0020] Particularly preferred tridentate ligands include compounds selected from the group of compounds represented by the following formulae: [ka]

[0021] The type of transition metal is not particularly limited. Specific examples include copper, chromium, cadmium, zinc, and cobalt. The valence of the transition metal is not particularly limited, but is preferably divalent from the viewpoint of ease of synthesis of PCN crystals. Although it is possible to use multiple types of transition metals, it is preferable to use a single one from the viewpoint of ease of structural analysis.

[0022] Examples of the ligand of the connector molecule include heteroatoms such as nitrogen atoms, oxygen atoms, and phosphorus atoms. The nitrogen atom can be, for example, the nitrogen of an amino group or a pyridinyl group. The oxygen atom can be, for example, the oxygen of a carboxy group, a carbonyl group, a hydroxyl group, or a nitro group. The phosphorus atom can be, for example, the phosphorus of a phenylphosphine group. The angle formed between each ligand of the bidentate ligand of the connector molecule and the center of gravity of the connector molecule is preferably 90° or more, more preferably 110° or more, even more preferably 140° or more, and particularly preferably 160° or more.

[0023] Suitable examples of the connector molecule include the following compounds: [ka]

[0024] The PCN crystal of this embodiment can take various forms. FIG. 2 shows an example of a structural unit of a PCN crystal, and FIG. 3 shows a structural diagram of a part of this PCN crystal. In the example of FIG. 2, the structural unit of the PCN crystal 1 is composed of four transition metals 3 (Co 2+ ) is coordinated to two tridentate ligands 2 and three connector molecules 4 (carboxy groups of terephthalic acid). In addition, two solvent molecules 5 (DMF) are coordinated to the transition metal. In the example of FIG. 3, the pores are arranged in a honeycomb shape, and have a three-dimensional network structure having hexagonal pores 6. From the viewpoint of the stability of the PCN crystal, it is preferable that the hexagonal openings of the two-dimensional network are hexagonal from a macroscopic viewpoint.

[0025] Furthermore, in the PCN crystal in Figure 2, two DMF molecules, which are the solvent molecules used during synthesis, are coordinated to the cobalt ion per unit structure. It is preferable that the bond between the solvent molecule incorporated into such a unit crystal and the transition metal is weaker than the coordinate bond between the transition metal and the tridentate ligand and the coordinate bond between the transition metal and the connector molecule. By incorporating such a solvent molecule into the crystal structure unit, it is expected that the structural fluctuation during the analysis of the guest molecule will be reduced and the analytical accuracy will be improved. In addition, it will be possible to replace the solvent depending on the guest molecule to be incorporated, which is expected to increase the number of analysis targets. Furthermore, it will be possible to confirm these solvent molecules inside the pores through analysis.

[0026] Fig. 2 PCN crystal 1 Co 2+ Coordinates to the nitrogen atom of the 3-pyridinyl group of the tridentate ligand and the carboxyl group of terephthalic acid, as shown in the enlarged partial view of Figure 5. In this example, two of the 3-pyridinyl groups of the tridentate ligand are positioned close to each other as shown in Figure 4, and Co 2+ The PCN crystal 1 is fixed by one terephthalic acid via the 3-pyridinyl group. In this way, the tridentate ligand 2 of the PCN crystal 1 is fixed in a structure with low symmetry. The use of the 3-pyridinyl group suppresses structural fluctuation, rigidifies the framework structure, and increases the periodicity of the structure, thereby improving the crystallinity. This makes it possible to provide a crystal that is suitable for structural analysis.

[0027] The shape of the pores can be adjusted by changing the structure of the connector molecule and the structure of the tridentate ligand. The size of the pores, expressed as the diagonal distance when the pores not filled with spheres of the van der Waals radius of the atoms forming the network structure are regarded as cubes, is, for example, 0.8 to 1.2 nm. The maximum diameter of the pores of the PCN crystal, which is defined as the short-axis distance when a cut is made at the opening of the pore and the cut is regarded as a rectangle, is not limited, but is preferably 1.5 to 5.0 nm from the viewpoint of use as a sample for crystal structure analysis. More preferably, it is 2.0 to 5.0 nm, and even more preferably, it is 2.5 to 5.0 nm. The opening diameter of the pores is mainly determined by the type of tridentate ligand. By making the size of the opening diameter of the pores of the two-dimensional network 1.5 nm or more, it is possible to selectively incorporate compounds with molecular weights of, for example, about 100 to 7000 into the hollow, making it possible to apply it to various uses including crystal structure analysis.

[0028] The PCN crystal according to this embodiment is suitable as a crystal for analyzing the crystal structure of guest molecules with high molecular weights, such as drugs and peptides. In addition, as shown in FIG. 2, by forming a crystal having an organic solvent as a ligand, the position of the guest molecule relative to the solvent molecule can also be analyzed. Furthermore, by making the bond between this organic solvent and the transition metal weaker than the coordinate bond between the tridentate ligand and the transition metal, and between the connector molecule and the transition metal, the degree of freedom to replace with other solvent molecules can be increased. Therefore, it is possible to adjust the environmental field of the pores of the PCN crystal according to the guest molecule. These effects are expected to improve the accuracy of crystal structure analysis.

[0029] Although the above examples show its use for analysis, it is also suitable for applications such as purification of substances and reaction fields in closed spaces. In addition, since its surface area is significantly larger than that of zeolites, it can be used as an adsorbent and for purification. It can also be used for sensing organic substances, i.e. as a chemical sensor material. It can also be used in drug delivery systems that release adsorbed guest molecules in response to external stimuli such as UV light.

[0030] (Manufacturing method) Next, an example of a method for producing a PCN crystal will be described, although the method for producing a PCN crystal of the present invention is not limited to the following method.

[0031] First, a tridentate ligand, a transition metal or transition metal compound, and a connector molecule are placed in a container and heated, and then the PCN can be synthesized by the solvothermal method. This allows the production of pore-containing PCN crystals by a one-pot reaction in a self-organizing manner. After the synthesis of PCN, the crystals can be obtained by thorough washing. Instead of the solvothermal method, PCN can be synthesized by the solution diffusion method, electrochemical synthesis method, microwave irradiation method, mechanochemical synthesis method, or ultrasonic synthesis method. Various PCNs can be synthesized by changing the solvent and its concentration, the molar ratio of the metal to the ligand, the temperature, and the metal ion.

[0032] The molar ratio of the tridentate ligand to the transition metal used is 1:1 to 1:10, preferably 1:1 to 1:5, more preferably 1:1 to 1:3. The molar ratio of the connector molecule to the transition metal is 1:1 to 1:7, preferably 1:1 to 1:5, more preferably 1:1 to 1:3.

[0033] The organic solvent used is not particularly limited as long as it can dissolve the tridentate ligand and the transition metal uniformly. Examples of the solvent include aromatic hydrocarbons such as benzene, toluene, xylene, chlorobenzene, 1,2-dichlorobenzene, mesitylene, and nitrobenzene; sulfoxides such as dimethyl sulfoxide (DMSO); amides such as N,N-dimethylformamide; ethers such as tetrahydrofuran, 1,2-dimethoxyethane, and 1,4-dioxane; alcohols such as methanol, ethanol, and isopropyl alcohol; and ketones such as acetone and methyl ethyl ketone. The solvent may be used alone or in combination of two or more. Among these, aromatic hydrocarbons are preferred as the solvent for the transition metal compound, and nitrobenzene is more preferred, because the porous network complex of the present invention can be synthesized in a higher yield. Furthermore, aromatic hydrocarbons and sulfoxides are preferred as the solvent for the tridentate organic ligand, and sulfoxides are particularly preferred.

[0034] The precipitated PCN crystals can be collected by filtration. The structure of the PCN crystals can be confirmed by elemental analysis, IR, UV absorption spectroscopy, visible light absorption spectroscopy, and X-ray single crystal structure analysis.

[0035] (Method of preparing samples for crystal structure analysis) Next, a method for preparing a sample for crystal structure analysis according to the present embodiment will be described. The preparation of the sample for crystal structure analysis according to the present embodiment involves incorporating a compound to be analyzed into the pores of the PCN crystal of the present embodiment, and using the compound as a sample for structure analysis.

[0036] First, a sample is prepared by dissolving a compound to be analyzed in a solvent, and the PCN crystal according to the present embodiment is dispersed in the sample. The compound to be analyzed is then incorporated into the pores of the PCN crystal, and the solvent is distilled off to produce the sample.

[0037] A method for bringing a mixture containing a compound to be analyzed into contact with a PCN crystal and incorporating molecules of the compound to be analyzed into the pores of the PCN crystal can be carried out by a known method.

[0038] The compound to be analyzed is not particularly limited as long as it is of a size that can enter the pores of the PCN crystal. It can be applied to a wide variety of compounds such as low molecular weight compounds, medium molecular weight compounds such as pharmaceuticals, and chiral compounds. For example, molecules with a molecular weight of about 50 to 7000 can be analyzed. Preferably, the compound is 5000 or less, more preferably 480 to 4000, and particularly preferably 500 to 3000.

[0039] The method of contacting the PCN crystal with the target compound is not particularly limited. For example, a method of preparing a solution of the target compound and contacting the PCN crystal with this solution, or when the target compound is liquid or gas, a method of directly contacting the PCN crystal with the target compound can be used to incorporate the molecules of the target compound into the pores of the PCN crystal. Among these, the method of preparing a solution of the target compound and contacting the PCN crystal with this solution is preferred because it is easier to obtain a better quality crystal structure analysis sample.

[0040] Furthermore, when a solution containing the compound to be analyzed is used or when the compound to be analyzed is liquid, the contact operation can be performed by immersing the single crystal in a solution containing the compound to be analyzed, or by packing the single crystal into a capillary and then passing a solution containing the compound to be analyzed through the capillary.

[0041] The solvent of the solution containing the target compound may be any solvent that does not dissolve the single crystal used and dissolves the target compound. Examples of organic solvents include aromatic hydrocarbons such as benzene, toluene, xylene, chlorobenzene, 1,2-dichlorobenzene, nitrobenzene, and mesitylene; aliphatic hydrocarbons such as n-butane, n-pentane, n-hexane, and n-heptane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and cycloheptane; nitriles such as acetonitrile and benzonitrile; sulfoxides such as dimethyl sulfoxide (DMSO); amides such as N,N-dimethylformamide and n-methylpyrrolidone; ethers such as diethyl ether, tetrahydrofuran, 1,2-dimethoxyethane, and 1,4-dioxane; alcohols such as methanol, ethanol, and isopropyl alcohol; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; halogenated hydrocarbons such as dichloromethane, chloroform, carbon tetrachloride, and 1,2-dichloroethane; esters such as methyl acetate, ethyl acetate, ethyl lactate, and ethyl propionate; and water. The solvents can be used alone or in combination of two or more.

[0042] The contact time between the compound to be analyzed and the PCN crystal according to this embodiment is not particularly limited, but is usually several minutes to several days. Depending on the compound, the contact time can be shortened or lengthened as appropriate. The contact temperature can be, for example, in the range of -30 to 200°C, and is not particularly limited. It is preferable to contact the compound to be analyzed at a temperature at which the compound can be easily handled.

[0043] A sample for crystal structure analysis is a sample in which molecules of a compound to be analyzed are incorporated into the pores of a PCN crystal. Due to the size of the opening diameter of the pores, the compound to be analyzed is regularly arranged in the pores. Regularly arranged here means that the molecules of the compound to be analyzed are incorporated into the pores to an extent that the structure can be determined by crystal structure analysis.

[0044] The sample for crystal structure analysis may be one that can determine the molecular structure of the compound to be analyzed, and it is not necessary that the molecules of the compound to be analyzed are incorporated into all the pores of the PCN crystal. The molecular structure of the compound to be analyzed is determined by performing crystal structure analysis of the compound to be analyzed using the above-mentioned sample for crystal structure analysis. X-ray diffraction, neutron diffraction, etc. can be used for the structure analysis. The molecular structure of the compound to be analyzed can be determined by performing crystal structure analysis using the sample for crystal structure analysis obtained by the method for preparing a sample for crystal structure analysis.

[0045] [Example] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0046] (Experimental Example 1) [Synthesis of 2,5,8-tri(3'-pyridyl)-1,3,4,6,7,9-hexaazaphenalene potassium (3-TPHAPK)] 4.1 g (26.0 mmol) of 3-amidinopyridine hydrochloride and 0.86 g (6.7 mmol) of potassium tricyanomethide were mixed thoroughly in a mortar, then transferred to a pressure-resistant container and heated at 180°C for 20 hours. The resulting black solid was transferred to a mortar and crushed to reduce particle size, and then added 300 cm of distilled water.3 The mixture was stirred at room temperature for 3 hours and filtered. Then, impurities were extracted using ethyl acetate until the organic layer became colorless. Then, the aqueous layer was dried using a rotary evaporator. The obtained brown solid was dissolved in 5M hydrochloric acid to a saturated solution. Then, 5M potassium hydroxide aqueous solution was added dropwise little by little until the precipitation of solids stopped. The precipitated solid was filtered. The obtained solid was dissolved in methanol, and acetone was added in an amount three times that of the solution, filtered, and the filtrate was dried under reduced pressure to obtain 286 mg (0.65 mol, yield: 9%) of an ochre powder.

[0047] The results of NMR and elemental analysis are as follows, and it was confirmed that the compound represented by formula (VI) was obtained. [ka] 1 H NMR: δ = 7.55 (ddd, 3H, J = 0.8, 4.8, 8.0Hz ), 8.69 (dd, 3H, J = 2.0, 8.6 Hz), 8.78 (dt, J = 2.0, 8.4 Hz), 9.61 (d, 3H, J = 2.8 Hz). 13 CNMR: δ 103.0, 123.7, 134.6, 135.9, 149.7, 151.7, 166.4, 166.7. calcd. (%) for C 22.7 H 23.08 KN 9 O 4.84 (=C 22 H 12 N 9 K (CH 4 O) 0.70 (H 2 O) 4.14 ): C, 50.63; H,4.32; N,23.41;. Found: C, 50.63; H,4.09; N, 23.41.

[0048] [Synthesis of PCN] Next, 15.8 mg (35.82 μmol) of the above 3-KTPHAP, 17.9 mg (107.7 μmol) of terephthalic acid (BDC), and 25.1 mg (193.3 μmol) of cobalt (II) chloride were placed in a pressure vessel, and dehydrated DMF was poured into the vessel at 10 cm 3The reaction was carried out at 80° C. for 7 days to obtain 45.1 mg (17.5 μmol) of reddish purple crystals in a yield of 97.7%. The results of the elemental analysis are shown below. calcd (%) for Co4C98.45H140.15N32.55(= Co4C92H92N26O16(C3H7NO)2.15(H2O)16.55): C, 45.96; H,5.49; N,15.33;. Found: C, 45.96; H, 5.49; N, 15.55.

[0049] [PCN crystal structure] FIG. 6 shows the powder X-ray profile of the PCN crystal according to Example 1. FIG. 6(a) shows the X-ray profile of the PCN crystal according to Example 1, FIG. 6(b) shows the X-ray profile of the PCN crystal of Example 1 after crushing it in a mortar, and FIG. 6(c) shows the X-ray profile by simulation. In FIG. 6(a), the measurement was performed as a single crystal, so it is considered that there is a part where the relative intensity is different from the simulation of the single crystal due to the occurrence of preferential orientation. On the other hand, in FIG. 6(b), it was confirmed that the peak at 20° is small and the graph is close to the simulation. It can also be inferred that the PCN crystal is obtained with a higher purity than the result of FIG. 6(b).

[0050] A unit structure diagram of the PCN crystal obtained from the X-ray structure analysis in Example 1 is shown in Figure 2, and an electron microscope photograph of the PCN crystal of Example 1 is shown in Figure 7. In 3-TPHAP (2,5,8-tri(3'-pyridyl)-1,3,4,6,7,9-hexaazaphenalene) in the PCN crystal of Example 1, the 3-pyridinyl group is fixed in a less symmetrical arrangement as shown in Figure 4, and the topology of the PCN crystal structure was 3,6-c. This 3,6-c topology has not been reported in any PCN crystals before.

[0051] 8 to 10 show structural diagrams for explaining the molecular arrangement of the PCN crystal of Example 1. FIG. 8 is a structural diagram of the PCN crystal as viewed from the c-axis direction (the long axis direction of terephthalic acid), and FIG. 9 is a structural diagram in which 3-TPHAP is hidden in FIG. 8, that is, a structural diagram as viewed from the c-axis direction. FIG. 10 is a structural diagram (top view) in the b-axis direction (stacking direction of 3-TPHAP) with 3-TPHAP hidden from the PCN crystal. From these figures, it can be seen that in the PCN crystal, terephthalic acid (BDC), which is a connector molecule, and cobalt ions form a two-dimensional sheet with a honeycomb structure, and 3-TPHAP is crosslinked between them to construct a three-dimensional structure. Two Co bonds to terephthalic acid. 2+ was found to be 10.4 Å, which is roughly consistent with the distance between the nitrogen atoms of the 3-pyridinyl group of the tridentate ligand.

[0052] The pore size of the PCN crystal of Example 1 was 8.3×12.5 Å in maximum opening size, and the porosity was 48.8%. Furthermore, it was confirmed that DMF was coordinated to the cobalt ions, and this DMF was regularly aligned in the PCN crystal. The coordination of DMF has the advantage that the analysis of guest molecules can be easily performed. Four molecules of this DMF are contained in the unit crystal structure, and this is a site with relatively weak bonds with transition metals. Therefore, it is possible to replace DMF with other solvents from the unit crystal structure, or to remove DMF by heat.

[0053] As shown in FIG. 5, the PCN crystal of Example 1 is 2+ It was confirmed that the ligands are asymmetrically coordinated, and that the DMF, which is a labile ligand, is adjacent to each other. 2+ The distance between DMF1 and Co is 2.0962 Å. 2+ The distance between DMF1 and DMF2 was 2.1230 Å. This result shows that there is a difference in the strength of the coordinate bond between the two DMFs. Of these, DMF2 has a longer bond length, so it is thought to be a weaker bond.

[0054] FIG. 11 shows the Co phase of one of the PCN crystals of Example 1. 2+This is a diagram of the structure of a PCN crystal in which one of the DMF coordinated to Co is replaced with water. 2+ The distance between Co and DMF is 2.102 Å. 2+ The distance between the water and the water molecule was 2.57 Å. The structure of the PCN crystal of Example 1 determined by X-ray structural analysis is shown in Table 1. The values ​​in parentheses indicate statistical errors for the values ​​in the table.

[0055] [Table 1]

[0056] FIG. 12 shows the TG-DTA profile of the PCN crystal according to Example 1. From the figure, it was confirmed that the crystal was stable up to about 400°C. It is believed that DMF, which is the solvent on the surface and in the pores, is released up to 100°C, and then the coordinated DMF is released around 200°C. It is also believed that the coordinated connector molecule is released around 400°C.

[0057] [Guest molecule analysis] Example 2 Next, a sample for crystal structure analysis was prepared using the PCN crystal according to Example 1. First, the PCN crystal of Example 1 was washed three times with DMF. Then, the PCN crystal was added to an anthracene saturated solution using DMF as a solvent, and anthracene was included in the PCN crystal. After 4 days, the structure was analyzed by single crystal X-ray structure analysis (Synchrotron PAL-2D).

[0058] Fig. 13 shows a structural diagram by X-ray structural analysis when anthracene is incorporated as a guest molecule into the PCN crystal of Example 1. The structure obtained by X-ray structural analysis of the PCN crystal of Example 2 is shown in Table 2. The values ​​in parentheses indicate statistical errors for the values ​​in the table.

[0059] [Table 2]

[0060] As is clear from Figure 13, no interactions such as hydrogen bonds or CH···π were observed between the PCN crystals and anthracene. This means that the anthracene molecules are incorporated in a solvated state in the solvent DMF. In this way, this method has the excellent effect of mitigating the influence of interactions derived from the PCN crystal structure and enabling the analysis of guest molecules.

[0061] Example 3 An example of an embodiment in which iodine was incorporated into the PCN crystal according to Example 1 will be described. 3 Weighed out the mixture and added 1.7 mg of PCN crystals to it. The results of iodine adsorption, that is, the profile of the change in absorption spectrum over time, are shown in Figure 14(a). As time passed, the absorption of the DMF-iodine complex decreased, indicating that iodine was being taken up by the PCN crystals.

[0062] Next, a sample in which sufficient PCN crystals were added to a DMF solution of iodine was irradiated with UV light. As a result, as shown in Figure 15, it was confirmed that the peak of the iodine-DMF association increased with increasing UV irradiation time. This did not occur in the iodine-containing DMF solution without PCN crystals, suggesting that the iodine incorporated in the PCN crystals was released from the pores by the UV light.

[0063] After iodine was released from the PCN crystals by UV light irradiation, iodine was again observed to be incorporated into the PCN crystals by turning off the UV light irradiation. It was also confirmed that the rate at which iodine was adsorbed into the PCN crystals remained almost unchanged compared to the initial time. These results show that UV light irradiation maintained the porosity of the PCN crystals unchanged, and that the release and inclusion of iodine can be controlled by UV light while maintaining the porosity.

[0064] Example 4 An example of an embodiment in which triphenylene was incorporated into the PCN crystal according to Example 1 will be described. First, the PCN crystal of Example 1 was immersed in ethyl acetate to exchange the solvent. Then, the PCN crystal was added to a triphenylene saturated solution in which ethyl acetate was used as a solvent, and anthracene was included in the PCN crystal. After 7 days, the structure was analyzed by single crystal X-ray structure analysis.

[0065] As is clear from Figure 16, no interactions such as hydrogen bonds or CH···π were observed between the PCN crystal and triphenylene. This means that the triphenylene molecules are incorporated in a solvated state in the solvent ethyl acetate. In this way, this method has the excellent effect of mitigating the influence of interactions derived from the PCN crystal structure and enabling the analysis of guest molecules.

[0066] [Table 3]

[0067] Example 5 An example of an embodiment in which carthamin, a medium molecule, was incorporated into the PCN crystal according to Example 1 will be described. First, about 0.8 mg of carthamin was dissolved in a solution containing 0.9 μL of DMF and 0.1 μL of water. Then, the PCN crystal according to Example 1 was added together with DMF, a storage solvent, to thereby encapsulate carthamin in the PCN crystal. After 7 days, the structure was analyzed by single crystal X-ray structure analysis.

[0068] As is clear from Figure 17, the PCN crystal can capture the solvated state, making it possible to analyze the structure of medium-sized molecules. [Table 4] [Explanation of symbols]

[0069] 1. PCN crystals 2 tridentate ligand 3 Transition metals 4. Connector molecules 5 Solvent molecules 6 Pore

Claims

1. A porous network complex crystal for guest molecule analysis, comprising: It has a three-dimensional network structure and has pores that contain guest molecules. the three-dimensional network structure is formed by coordinating a tridentate ligand and a connector molecule to a transition metal; The tridentate ligand is a compound having a three-branched structure represented by the following general formula (I) in which the nitrogen atoms of the 3-pyridinyl group each function as a ligand (wherein W is an aromatic group which may contain a heteroatom): 【Chemistry 1】 the connector molecule is a bidentate ligand, and each ligand of the bidentate ligand forms an angle with the center of gravity of the connector molecule of 70 to 180°; A porous network complex crystal for analyzing guest molecules in which the free rotation of the 3-pyridinyl group axis is restricted.

2. The porous network complex crystal for guest molecule analysis described in claim 1, wherein a solvent molecule is further coordinated to the transition metal, and the coordinate bond between the transition metal and the solvent molecule is weaker than the coordinate bonds between the transition metal and the tridentate ligand and between the transition metal and the connector molecule.

3. 3. The porous network complex crystal for guest molecule analysis according to claim 1, wherein the transition metal is a divalent metal.

4. The porous network complex crystal for guest molecule analysis according to any one of claims 1 to 3, wherein the pores include honeycomb-shaped pores and pores that are smaller in size than the honeycomb-shaped pores and connect the honeycomb-shaped pores to each other.

5. The porous network complex crystal for guest molecule analysis according to any one of claims 1 to 4, wherein the tridentate ligand is represented by general formula (II): 【Chemistry 2】 In the formula (II), X is selected from the group consisting of the compounds represented by the formula (III) and the compounds represented by the formula (IV), and Y 1 ~Y 3 are each independently selected from a single bond, a carbon-carbon double bond, and a carbon-carbon triple bond directly connecting X to the 3-pyridinyl group. 【Chemistry 3】 However, Z in the general formula (III) 1 ~Z 6 are each independently CH or N. 【Chemistry 4】

6. The porous network complex crystal for guest molecule analysis according to any one of claims 1 to 5, wherein the guest molecule has a medium molecular weight of 500 to 3,000.

7. Prepare a sample by dissolving the target compound in a solvent. The sample is Dispersing the porous network complex crystal for guest molecule analysis according to any one of claims 1 to 6; A method for preparing a sample for crystal structure analysis, comprising incorporating the compound to be analyzed into the pores of the porous network complex crystal.

8. 8. A method for determining the molecular structure of a compound to be analyzed, comprising carrying out crystal structure analysis using a sample for crystal structure analysis obtained by the method for preparing a sample for crystal structure analysis according to claim 7.

Citation Information

Patent Citations

  • Porous network complex crystal for guest molecule analysis, method for preparing sample for crystal structure analysis, and method for determining molecular structure

    JP7626419B2

  • Single crystal of porous compound, method for assessing quality of single crystal, method for preparing solution including compound to be analyzed, method for producing crystal structure analysis sample, and method for determining molecular structure of compound to be analyzed

    WO2016143872A1